Postoperative expressive aphasia associated with intravenous midazolam administration: a 5-year retrospective case-control study. Issue 8 (August 2020) - Oh, Saecheol; Chung, Jihyun; Baek, Sujin; Park, Yoo Jung
Objectives: This study aimed to investigate the epidemiology of intravenous midazolam-induced postoperative expressive aphasia (EA). Methods: The incidence rate, risk ratio, and contributing factors to intravenous midazolam-induced postoperative EA were analyzed retrospectively in 6756 orthopedic patients. A telephone interview was conducted with patients with EA after surgery. Results: Patients were allocated to either the midazolam group (n = 6178) or no-midazolam group (n = 578). Twelve patients developed EA in the midazolam group, with an incidence of 0.19%, and no patient developed EA in the no-midazolam group. The mean age of EA patients was 70 years, and 92% were women. Among them, 75% received general anesthesia, and the mean dose of midazolam was 1.8 mg. EA was reversed in nine of 12 (75%) patients within 4 minutes of flumazenil administration, and >60 minutes were required to reverse EA in the other three patients (25%). Conclusion: Intravenous midazolam administration for preoperative sedation caused transient EA in 0.19% of patients, especially elderly women who received general anesthesia, and EA could be reversed by flumazenil.